Global participation in sport and leisure-time physical activities: A systematic review and meta-analysis - Hulteen, Ryan M.; Smith, Jordan J.; Morgan, Philip J.; Barnett, Lisa M.; Hallal, Pedro C.; Colyvas, Kim; Lubans, David R. (Preventive medicine, 2017)
This review aimed to determine the most popular physical activities performed by children, adolescents, and adults globally. Statistic bureau websites and article databases Scopus, ProQuest, SPORTDiscus, and Science Direct were searched between November 17th, 2014 and April 31st, 2015. Eligible studies were published in the last 10years with participation rates for specific physical activities among individuals five years or older. Data extraction for included articles (n=64) was assessed independently and agreed upon by two authors. A random-effects model was used to calculate participation rates in specific activities for each age group and region. In total 73,304 articles were retrieved and 64 articles representing 47 countries were included in the final meta-analysis. Among adults, walking was the most popular activity in the Americas (18.9%; 95% CI 10.2 to 32.5), Eastern Mediterranean (15.0%; 95% CI 5.8 to 33.6), Southeast Asia (39.3%; 95% CI 0.9 to 98.0) and Western Pacific (41.8%; 95% CI 25.2 to 60.6). In Europe and Africa, soccer (10.0%; 95% CI 6.5 to 15.1) and running (9.3%; 95% CI 0.9 to 53.9), respectively, were top activities. Child and adolescent participation results were highly dependent upon region. American youth team sport participation was high, while youth from the Eastern Mediterranean and Western Pacific were more likely to report participation in lifelong physical activities. Global data for adults reflects a consistent pattern of participation in running and walking. Among all age groups and regions soccer was popular. In children and adolescents, preferences were variable between regions. •Walking was the most popular physical activity among adults in four of six regions.•Soccer, running, walking and athletics were a top choice of activity for adolescents.•Running and soccer were the most commonly reported activities for children.•The Eastern Mediterranean, Southeast Asia and Africa lack quality physical activity data.